The adoption of mobile commerce in Malaysia: an exploratory study on the extension of theory of planned behavior - Noordin, Mohamad Fauzan; Sadi, A.H.M. Saifullah (University of Delhi, Shri Ram College of Commerce, 2010)
Mobile Commerce also known as M-commerce is thought to be the next big phase in technologically dependent society after following E-commerce era. Mobile commerce has been a huge success in terms of individuals’ adoption in some markets like Korea, Hong Kong, and Japan while surprisingly, not as flourishing in others. However, its adoption and level of use is low in Malaysia compared to others nations such as Korea, Singapore and Japan. Prior studies have been conducted using traditional adoption models and theories (such as TAM) that mainly focus on technology aspects. This study aims to identify some factors that affect the adoption of M-commerce in Malaysia by developing M-commerce adoption Model based on traditional technology model such as Theory of Reason Action (TRA), Theory of Planned Behavior (TPB),Technology Acceptance Model (TAM) and Diffusion Innovation theory (DOI). The findings revealed that Perceived Usefulness, Perceived Ease of Use, Perceived trust are positively associated with consumer attitude towards use M-commerce which is affecting consumer intention to use. Personal innovativeness and perceived cost were found to have insignificant effect on consumer attitude towards use. In addition, Social Influence and self-control are affecting subjective norm which has significant affect consumer intention to use m-commerce. Self-efficacy and facilitating condition are also affecting perceived behavioral control which has strong relationship with consumer intention to use m-commerce. The findings made a contribution, allowing us to understand the factors that can affect the adoption of m-commerce. The study successfully extended TPB and TAM model with Subjective norm and personal behavioral control to represent a model for the adoption of m-commerce in Malaysia.